Controlling shareholders, audit committee characteristics, and related party transaction disclosure: Evidence from Indonesia - Dwi Ernawati; Y. Anni Aryani (University of Merdeka Malang, 2019)
The disclosure of related party transactions was required in the financial statements because it is potentially misused by controlling shareholders. This study aims to examine controlling shareholders, audit committee characteristics, and related party transaction disclosure. The controlling shareholders are proxied by the family share ownership and the proportion of the controlling shareholder family members on the board of directors. The samples used in this study are family companies listed on the Indonesia Stock Exchange (IDX) in the year 2017. In this study, the multiple regressions were used to test the hypothesis. We found that controlling shareholders have a negative influence on related party transaction disclosure. Meanwhile, accounting expertise of the audit committee has a positive influence on related party transaction disclosure. Our result show companies that controlled by the family have low motivation to disclose related party transaction disclosure. However, accounting expertise audit committee may encourage companies to disclose related party transactions.JEL Classifications: G32, G34DOI: https://doi.org/10.26905/jkdp.v23i1.2701